KONSEP DAN PRAKTEK MANAJEMEN DALAM ORGANISASI OLAHRAGA - Venli Pelle; Christo Rompis; Augustinus Robin Butarbutar (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Management in the context of sports organizations is a series of activities that involve planning, organizing, mobilizing and controlling the energy resources owned by the organization to achieve certain goals. The concept of management in sports organizations involves a deep understanding of general management theories, but adapted to the unique characteristics of the world of sports. Management in the context of sports organizations is the implementation of controlling and coordinating human, physical and financial resources to achieve regulated goals.